Treatment of identical twins with congenitally missing maxillary lateral incisors - a long-term follow-up - Wechsler Morris H.; Van Dong Phung (Sciendo, 2018)
Congenitally missing upper lateral incisors can significantly alter the aesthetic appearance of a smile. The orthodontic challenge is to achieve acceptable facial aesthetics by restoring the dentition either by replacing the missing teeth or by substituting the canines for the lateral incisors. The present case report discusses the orthodontic treatment of two identical twin sisters with missing upper lateral incisors, in whom the spaces were reopened to accommodate prosthetic replacement. The rationale for this treatment alternative is discussed.